The view of knowledge: An institutional theory of differences in educational quality - Magnus Henrekson; Johan Wennström (Research Institute of Industrial Economics (IFN), 2022)
This essay argues that the most crucial institution of any school system is its view of knowledge - from which virtually all other aspects of a school are derived: the content of its curricula, its pedagogical practices, and the incentives that motivate its members. To make this case, we outline the two main conflicting views of knowledge, the classical view and the postmodern social constructivist view. According to the classical view, the purpose of schooling is to give students objective knowledge and skills that they cannot acquire in any way other than through hierarchical instruction in well-defined disciplines. The social constructivist view rejects the existence of objective knowledge. This rejection translates to a preference for student-directed pedagogy, the mixing of instructional fields, and an emphasis on developing general critical thinking skills rather than on acquiring domain-specific knowledge. Using the history of education in Sweden as an example, our analysis suggests that the recent decline in educational quality in the Western democracies can be remedied by a paradigm shift in the governing view of knowledge toward the classical view.
Keywords: H42; H44; H75; I22; I28; L88; 330; Communal knowledge; institutions; postmodernism; social constructivism; thought style; views of knowledge